BIOPHYSICAL PROPERTIES OF MONOCYTES INDICATE DISEASE ACTIVITY, SEVERITY OF FIBROTIC OR MICROVASCULAR MANIFESTATIONS AND THE RISK FOR PROGRESSION IN SYSTEMIC SCLEROSIS - Matei, Alexandru-Emil; Marketa, K.; Xu, L.; Györfi, Andrea-Hermina; Boxberger, E.; Soteriou, D.; Papava, Maria; Prater, Julia; Hong, Xuezhi; Kraeter, M.; Schett, Georg; Guck, J.; et al. (ANNALS OF THE RHEUMATIC DISEASES, 2022)
CRIS-Team WoS Importer:2022-11-04

Identification of a Distinct Monocyte-Driven Signature in Systemic Sclerosis Using Biophysical Phenotyping of Circulating Immune Cells - Matei, Alexandru-Emil; Kubankova, Marketa; Xu, Liyan; Györfi, Andrea-Hermina; Boxberger, Evgenia; Soteriou, Despina; Papava, Maria; Prater, Julia; Hong, Xuezhi; Bergmann, Christina; Kraeter, Martin; Schett, Georg; et al. (Arthritis and Rheumatology, 2023)
Objective Pathologically activated circulating immune cells, including monocytes, play major roles in systemic sclerosis (SSc). Their functional characterization can provide crucial information with direct clinical relevance. However, tools for the evaluation of pathologic immune cell activation and, in general, of clinical outcomes in SSc are scarce. Biophysical phenotyping (including characterization of cell mechanics and morphology) provides access to a novel, mostly unexplored layer of information regarding pathophysiologic immune cell activation. We hypothesized that the biophysical phenotyping of circulating immune cells, reflecting their pathologic activation, can be used as a clinical tool for the evaluation and risk stratification of patients with SSc.Methods We performed biophysical phenotyping of circulating immune cells by real-time fluorescence and deformability cytometry (RT-FDC) in 63 SSc patients, 59 rheumatoid arthritis (RA) patients, 28 antineutrophil cytoplasmic antibody-associated vasculitis (AAV) patients, and 22 age- and sex-matched healthy donors.Results We identified a specific signature of biophysical properties of circulating immune cells in SSc patients that was mainly driven by monocytes. Since it is absent in RA and AAV, this signature reflects an SSc-specific monocyte activation rather than general inflammation. The biophysical properties of monocytes indicate current disease activity, the extent of skin or lung fibrosis, and the severity of manifestations of microvascular damage, as well as the risk of disease progression in SSc patients.Conclusion Changes in the biophysical properties of circulating immune cells reflect their pathologic activation in SSc patients and are associated with clinical outcomes. As a high-throughput approach that requires minimal preparations, RT-FDC-based biophysical phenotyping of monocytes can serve as a tool for the evaluation and risk stratification of patients with SSc.
CRIS-Team WoS Importer:2023-04-14